The Effect of Gender on Violations and Errors in Risky Driving Behaviour Among Car Drivers: A Systematic Literature Review - Almira Rahma Safira; Dewi Maulina (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Risky driving behaviour significantly contributes to traffic accidents, with gender long recognized as an influencing internal factor. However, findings on gender’s role in driving behaviour are inconsistent. This systematic review explores gender’s influence on two risky driving categories, violations and errors, while considering cultural context and research methodologies. Following PRISMA guidelines, an initial search yielded 110 articles. After title screening, 62 remained, with subsequent abstract review narrowing the selection to a final 21 scientific articles published between 2015 and 2025, primarily from ScienceDirect. Results indicate that men tend to commit more offences, while women commit more errors, particularly in WEIRD countries. Furthermore, the utilized research designs influenced the generalizability of the findings. This study emphasizes the significance of cross-cultural approaches and appropriate design in gender-based traffic safety research, highlighting the need for targeted interventions. Keywords: culture, errors, gender, research methods, risky driving behaviour, violations